ANALISIS KESALAHAN SISWA PADA PERSAMAAN GARIS LURUS BERDASARKAN TAHAPAN KASTOLAN - Novitasari, Zulifah Dwi; Fitriani, Nelly (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This study aims to analyze student errors in solving straight line equations material problems through the Kastolan stages. The research method used is descriptive qualitative. The data collection technique was done by giving straight-line equation questions to students which were then analyzed for their answers to describe their errors based on the Kastolan stages. This research was conducted at one of the State MTs in Karawang in the 2020-2021 academic year. The subjects were 10 grade IX students. The results of the analysis of student answers obtained that there are 44% errors occur in conceptual errors, 73% errors in procedural errors, and 36.67% errors in technical errors. The factors that became the error were (1) not understanding the concept of solving problems, (2) the lack of students' ability to operate arithmetic operations, and (3) students getting used to working on questions that matched with the examples.